Structural organization of learning styles among students with different risk of internet-dependent behavior - Natalia A. Bembeeva; Alla K. Belousova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper presents empirical results of the study of the structural organization of learning styles among students with unequal risk of Internet-dependent behavior based on structural and psychological analysis. The purpose of this research was to study the structural organization of learning styles among students, taking into account the degree of risk of their Internet-dependent behavior. The features of students learning styles in the Internet space are analyzed. The relevance of the research is due to the fact that the introduction of the Internet into a persons life has changed his thinking and, in general, his image of the world. At the same time, the study of learning styles at the student age is of interest not only in scientific terms, but also in practical terms due to the active introduction of online learning and the use of information technologies in the learning process. The study used Chens CIAS methodology, D.Kolbs "Definition of learning style" methodology, "Thinking Style" methodology by A.K. Belousova. The study also used methods of mathematical and statistical processing of empirical data, in particular, structural and psychological analysis based on generalized indicators of the index of organization, integrativity and differentiation of the structure, the express-x^2 method for comparing matrices and structurograms for their "homogeneityheterogeneity", proposed by A.V. Karpov. The results of the study show that the values of the indices of the structural organization of the indicators of learning styles and Internet addiction differ among students with different risks of Internet-dependent behavior. The structural diagrams of the study indicators in all three identified groups of students with varying degrees of Internet-dependent behavior are heterogeneous. Thus, they have qualitative differences in the content of the relationships.